Remarks on greed (aneleutheria, illiberalitas) as a moral flaw in Aristotelis de virtutibus libellus by Franciscus Tidicaeus - Dreikopel, Tomasz (Folia Toruniensia, 2022)
The aim of this study is to present the reflections on greed as a moral flaw, which were included in the Aristotelis de virtutibus libellus of Franciscus Tidicaeus, then professor of the Academic Gymnasium in Toruń, published in 1609 in Leipzig. The work of the Toruń scholar contains an insightful and erudite exegesis of the essay On Virtues and Vices, preserved under the name of Aristotle. A comparison of the part of commentary we are interested in with the material contained in Aristotle's three ethical treatises leaves no doubt that Tidicaeus' remarks on this flaw reflect the moral teaching of his predecessor, constituting the starting point and at the same time the main goal of his arguments.